Lakon Punakawan as a Form of Religious and Cultural Transformation of Javanese Community - Fuad Noorzeha; Agus Sutono; John Abraham Ziswan Suryosumunar (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Wayang (puppet shows) for the Javanese people are a source of culture and tradition, philosophical values as well as religious teachings. It developed into a means of socio-cultural-religious transformation of da’wah, especially for Sunan Kalijaga. In the wayang, some lakon (plays, scenes, episodes) are taken from the epic story of the Ramayana, Mahabharata, and other ancient literatures. Meanwhile, wayang characters that resonate the Javanese people are Punakawan. The cultural and religious transformation brought by the lakon can be seen in the meaning and naming of Punakawan. In addition, the displayed role contains an elegant religious message wrapped in culture. Employing qualitative research using the analysis method, steps taken done to write the paper are; first, observing the theological and social revolution of the Javanese society, which is animist, dynamic, and paganist towards monotheistic mysticism. The second is the shift phenomena of Javanese Hindu ideology towards the Islamization of Java through an egalitarian concept of Islam. The third is the interpretation of young people’s anxiety through the distinctive voices of criticism. The result of this research is the disclosure of written descriptions of the characteristics of the practice of Javanese society through the process of cultural and religious transformation in the interpersonal play of Punakawan.